Optogenetic control of migration of contractile cells predicted by an active gel model - Drozdowski, Oliver; Ziebert, Falko; Schwarz, Ulrich S. (Communications Physics, 2023)
Cell crawling on flat substrates stems from intracellular flows of the actin cytoskeleton that are driven by both actin polymerization at the front and myosin contractility at the back. Optogenetics makes it experimentally possible to spatially control contraction and possibly cell migration too. Here we theoretically analyze this situation using a one-dimensional active gel model that reflects the property of myosin II to assemble into minifilaments. Our model predicts bistability between sessile and motile solutions when cell adhesion and contractility are sufficiently large and in balance. We show that one can switch between the different states at realistic parameter values via optogenetic activation or inhibition of contractility, in agreement with recent experiments performed for neutrophils in microchannels. We predict the required activation strengths and initiation times, compare the effects of local and global increases of myosin II levels, and show that actin polymerization alone can affect a switch in direction only at high strength.
Veröffentlicht: 30. Juni 2023
Gesehen am 24.08.2023